Spontaneous cerebrospinal fluid rhinorrhoea as the presenting feature of an invasive macroprolactinoma - Mankia, Satveer Kaur (BMJ Publishing Group, 2009)
A 29-year-old male university student, with no prior history of trauma, presented with a 1 year history of clear fluid leaking intermittently from his left nostril. His past medical history included bilateral gynaecomastia since age 12, and recent low libido. β2-transferrin analysis of the nasal fluid confirmed a diagnosis of cerebrospinal fluid (CSF) rhinorrhoea. The serum prolactin was grossly elevated at 42 700 mU/l and brain magnetic resonance imaging (MRI) revealed a large parasellar/sellar mass. A diagnosis of invasive macroprolactinoma complicated by spontaneous CSF rhinorrhoea was made. The patient was commenced on treatment with cabergoline, but while awaiting surgery to repair the CSF leak he developed streptococcus mitis and sanguis meningitis. He made an uncomplicated recovery with antibiotic treatment. Immediately following this episode, the CSF rhinorrhoea resolved spontaneously. Subsequently, a repeat MRI scan revealed dramatic involution of the pituitary mass and the serum prolactin had fallen to 604 mU/l.